Model Pendidikan Berbasis Karakter Religius di Madrasah Diniyah Takmiliyah - Koyin, Nur (Universitas Wahid Hasyim Semarang, 2023)
This research aims to examine madrasah diniyah takmiliyah from historical observations. This research is a type of qualitative research with a library approach. Research data was collected from books, documents and journals related to the research theme and then analysed. Data analysis is carried out by grouping data, reducing data, coding, looking for appropriate themes and analyzing them. The results of the research show that institutionally madrasah diniyah takmiliyah is a non-formal educational institution born from and for the community. Madrasah diniyah takmiliyah has the aim of instilling religious values in its students through habituation, through the model of kyai or teachers who teach and through intensive and continuous teaching of the Islamic religion.